2007
DOI: 10.1002/fld.1438
|View full text |Cite
|
Sign up to set email alerts
|

Particle transport method for convection problems with reaction and diffusion

Abstract: SUMMARYThe paper is devoted to the further development of the particle transport method for the convection problems with diffusion and reaction. Here, the particle transport method for a convection-reaction problem is combined with an Eulerian finite-element method for diffusion in the framework of the operator-splitting approach. The technique possesses a special spatial adaptivity to resolve solution singularities possible due to convection and reaction terms. A monotone projection technique is used to trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 30 publications
(42 reference statements)
0
8
0
Order By: Relevance
“…Moreover, the Eulerian FEM requires discrete physical information not only at the nodes but also at the Gaussian points to initialize the system (9). Therefore, in the following we define the necessary particle-to-grid and node-to-particle interpolation techniques.…”
Section: Interpolation Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the Eulerian FEM requires discrete physical information not only at the nodes but also at the Gaussian points to initialize the system (9). Therefore, in the following we define the necessary particle-to-grid and node-to-particle interpolation techniques.…”
Section: Interpolation Techniquesmentioning
confidence: 99%
“…The transfer of information is commonly achieved by interpolation or projection techniques (e.g. global vs local information, damped least-squares, etc, [9], [10]), which are generally problem-dependent and require careful design, as seemingly small errors during the interpolation process can accumulate rapidly due to the large number of interpolations performed during a typical simulation [11]. Also, while splitting the physical operators facilitates the implementation of different solvers within the numerical scheme (lending itself to parallel computing), and greatly simplifies the numerical procedure, traditional splitting techniques are typically unable to achieve high-order accuracy (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Boundary conditions of f = 0 were applied to the 'west' and 'south' boundaries, while ∂ f ∂n = 0 was applied to the remaining boundaries. The initial conditions were given by problem has the analytical solution [9] f = σ 0 f 0…”
Section: Propagation Of a Gaussian Pulsementioning
confidence: 99%
“…The LE method takes advantage of appropriate operator splitting techniques to solve different aspects of the physical model with most suitable Lagrangian or Eulerian formalism [24] . Shipilova et al [25] applied a LE method (the particle transform method) to solve the convection-diffusion-reaction problems, numerical results showed that the PTM can avoid the numerical oscillation even for a very sparse grid. So far, there is no attempt to use the LE approaches to deal with the spurious numerical propagation phenomenon generated in simulating the reacting flows.…”
Section: Introductionmentioning
confidence: 99%